2009
DOI: 10.1371/journal.pone.0006244
|View full text |Cite
|
Sign up to set email alerts
|

Calnexin Regulates Apoptosis Induced by Inositol Starvation in Fission Yeast

Abstract: Inositol is a precursor of numerous phospholipids and signalling molecules essential for the cell. Schizosaccharomyces pombe is naturally auxotroph for inositol as its genome does not have a homologue of the INO1 gene encoding inositol-1-phosphate synthase, the enzyme responsible for inositol biosynthesis. In this work, we demonstrate that inositol starvation in S. pombe causes cell death with apoptotic features. This apoptotic death is dependent on the metacaspase Pca1p and is affected by the UPR transducer I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 133 publications
2
30
4
Order By: Relevance
“…Since then, a pro-cell death role for Yca1 has been demonstrated in budding yeast cells in response to viral toxins and different types of abiotic and metabolic defect-associated stresses and chronological aging ( Table 2). 27 A similar requirement for a metacaspase has been reported in the fission yeast, albeit for a more limited number of cell death conditions, including lipotoxic stress 18 and inositol starvation 19 ( Table 2). Further in the fungi kingdom it has been established that both PaMca1 and PaMca2 are required for senescence-associated cell death in P. anserina, 23 a single Candida albicans metacaspase, CaMCA1, mediates oxidative stress-induced cell death in this pathogenic yeast, 28 whereas one of the two metacaspases, CasA, promotes ER stressassociated cell death in A. nidulans 25 (Table 2).…”
Section: Metacaspases In Cell Deathsupporting
confidence: 60%
See 1 more Smart Citation
“…Since then, a pro-cell death role for Yca1 has been demonstrated in budding yeast cells in response to viral toxins and different types of abiotic and metabolic defect-associated stresses and chronological aging ( Table 2). 27 A similar requirement for a metacaspase has been reported in the fission yeast, albeit for a more limited number of cell death conditions, including lipotoxic stress 18 and inositol starvation 19 ( Table 2). Further in the fungi kingdom it has been established that both PaMca1 and PaMca2 are required for senescence-associated cell death in P. anserina, 23 a single Candida albicans metacaspase, CaMCA1, mediates oxidative stress-induced cell death in this pathogenic yeast, 28 whereas one of the two metacaspases, CasA, promotes ER stressassociated cell death in A. nidulans 25 (Table 2).…”
Section: Metacaspases In Cell Deathsupporting
confidence: 60%
“…18,19 LmjMCA, a single metacaspase of Leishmania major, is involved in cell cycle regulation 20 and, when overexpressed, stimulates oxidative stress-induced cell death. 21 Further studies using corresponding deletion and inactivation mutants are required to determine whether the single metacaspases present in L. major and fission yeast are multifunctional proteins comparable to Yca1.…”
Section: Multifunctionality Functional Specialization or Redundancy mentioning
confidence: 99%
“…In recent years, it has been found that a number of unicellular organisms can also undergo apoptotic cell death. [1][2][3][4][5] In budding yeast Saccharomyces cerevisiae, apoptotic cell death was induced in response to several stimuli 2) in a manner dependent on 4) or independent of 5) metacaspase, the yeast homolog of metazoan caspases, while in fission yeast Schizosaccharomyces pombe, an evolutionarily distant relative of S. cerevisiae and a valuable tool for studying the basic cellular processes of higher eukaryotes, apoptotic cell death has been observed for relatively few stimuli, 6,7) and those stimuli are not those of S. cerevisiae. Considering the usefulness of comparative studies of S. cerevisiae and S. pombe for elucidating basic cellular mechanisms, to uncover a common agent inducing apoptotic death in both S. cerevisiae and S. pombe cells and identifying the mechanisms of cell death induced by the reagent are of critical importance.…”
mentioning
confidence: 99%
“…2 We thus had revealed that one metacaspase, YCA1, was involved in the same process as caspases, namely programmed cell death (PCD). Indeed, many groups subsequently unfolded the crucial contribution of metacaspases to cell death execution upon various stresses in yeast and other fungi, [3][4][5][6] as well as in plants. 7 Bozhkov, Zhivotovsky and colleagues 8 could even demonstrate that the plant metacaspase mcII-Pa shapes the embryo of Norway spruce (Picea abies) during development, presumably through its implication in developmental cell death.…”
mentioning
confidence: 99%